The Existence of Women in the Short Story “Forever Love” By Helvy Tiana Rosa - Rica Cahyani; Ari Kusmiatun (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
Forever love"is a short story by Helvy Tiana Rosa that discusses women's struggles in social life. The aim is to describe the existence of women in the social system, family and environment. The method used in this study is descriptive analysis with a qualitative research type and an existential feminist approach. The data were obtained from excerpts from the short story "Forever Love". The research technique was carried out in stages, namely determining data sources, collecting data, and grouping data. Data analysis techniques were carried out in stages such as reducing research data, presenting research data, and concluding research data. Based on the research results, researchers can find that women are inspirational about love, friendship, and hard work.